Effect of Use of Learning Media a Pictured Story on Abilities Reading Comprehension of Class IV Students UPT SD Negeri 067093 Medan - Jheni Yusuf Saragih, Nanda Ayu Setiawati, Winny Sunfriska Limbong, Clara Abigail Sitorus (Pusdikra-Publishing.com, 2021)
The purpose of this study is to determine the effect of using picture story on students’ reading comprehension ability of fourth grade students at UPT SDN 067093 Medan in academic. This research was Pre-Experimental Design. The research was conducted from May to June 2022. The sample was 26 students which was total of the population. The data collection techniques used in this research were test, documentation and observation. The results showed that there was an effect of picture story on students’ reading comprehension ability of fourth grade students at UPT SDN 067093 Medan in academic. It can be proven from the analysis results obtained using t-test showing that tcount > t table, 10,567 > 1.411, then Ho is rejected and Ha is accepted. It can be concluded that picture story affect on students’ reading comprehension ability of fourth grade students at UPT SDN 067093 Medan in academic.